2020
DOI: 10.1093/jamia/ocaa107
|View full text |Cite
|
Sign up to set email alerts
|

Mapping scientific landscapes in UMLS research: a scientometric review

Abstract: Objective The Unified Medical Language System (UMLS) is 1 of the most successful, collaborative efforts of terminology resource development in biomedicine. The present study aims to 1) survey historical footprints, emerging technologies, and the existing challenges in the use of UMLS resources and tools, and 2) present potential future directions. Materials and Methods We collected 10 469 bibliographic records published betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Because it is both an evolving set of artifacts and a set of ideas, it is hard to find, over the ensuing nearly 40 years, a large biomedical information project that has not been influenced by it. Today, as a testament to Lindberg's foresight, the UMLS is infrastructure -heavily used, but not always cited [12,[33][34]. As described here, it had no precedent, and, thus, initially, application developers, and their end-users, had difficulty applying it.…”
Section: Considering the Impact Of The Umlsmentioning
confidence: 99%
“…Because it is both an evolving set of artifacts and a set of ideas, it is hard to find, over the ensuing nearly 40 years, a large biomedical information project that has not been influenced by it. Today, as a testament to Lindberg's foresight, the UMLS is infrastructure -heavily used, but not always cited [12,[33][34]. As described here, it had no precedent, and, thus, initially, application developers, and their end-users, had difficulty applying it.…”
Section: Considering the Impact Of The Umlsmentioning
confidence: 99%
“…For example, Hernandez-Alvarez et al [23] used high-frequency keywords in abstracts, manually identified important terms to generate knowledge domains, and divided the literature into multiple knowledge domains by calculating the similarity between them to classify the literature. Similarly, Kim et al [25] used keywords and abstracts as raw data to create a document terminology matrix representing the frequency of terms in the accounting literature. Makabate et al [3] used a grounded theory approach to code the terms collected in the abstracts and classify research methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As mentioned, in the eld of information retrieval in medical sciences, until this research was done, no scientometric study or KMD has been conducted to analyze research in this eld. In the most relevant research, Kim et al have used KMD methods to examine historical footprints, emerging technologies, and challenges in using UMLS resources and tools to present potential future directions (Kim et al 2020). But KMD has been used in many studies in speci c elds of medical sciences.…”
Section: Mapping Knowledge Domainmentioning
confidence: 99%